South Pole Ice Core Holocene Major Ion Dataset - Winski, Dominic A. (IEDA: US Antarctic Program Data Center, 2020)
Abstract: This dataset includes major ion and seasonal sea salt chemistry data from the South Pole Ice Core. Included are the raw major ion data, annually resolved mean, maximum and minimum sea salt sodium concentrations and centennially resolved principal components (discussed in Winski et al. (in review).